India's Growth Story - Ahmad, Junaid Kamal; Blum, Florian; Gupta, Poonam; Jain, Dhruv (World Bank, Washington, DC, 2018)
India has attained much economic success in the past three decades. Yet an economic deceleration in recent years has generated worried commentaries about the country's growth outlook. This paper offers a long-term perspective on India's growth experience. Analyzing the past five decades of data, the paper notes that growth has slowly but steadily accelerated, become less erratic, and been well diversified across sectors and states. A more granular assessment of the period since the early 1990s finds that there were three distinct phases of growth: a period of slow acceleration from 1991 to the early 2000s; a short period of unusually rapid growth, with certain features of unsustainability, during 2004-08; and a corrective slowdown that started with the global financial crisis in 2008. The slowdown has been reflected most profoundly in investment, credit, and exports. Even as the economy has now recovered to a growth rate of 7 to 7.5 percent, durably accelerating it to a higher level will require a concerted policy momentum that succeeds in reversing the slowdown in investment, credit supply, and exports; and support from the global economy. Maintaining the hard-won macroeconomic stability, implementing a definite and durable solution to the banking sector issues, and realizing the expected growth and fiscal dividend from the Goods and Services Tax are some of the other factors that can help attain a higher growth rate.